The Role of Physical Activity in Improving Insulin Sensitivity: A Narrative Review - Muraszewski, Łukasz; Muraszewska, Emilia; Kwitowska, Patrycja; Pyjecka, Małgorzata; Ubysz, Eryk; Król, Agata; Lewandowska, Edyta; Łuczyński, Cezary; Paczkowski, Maciej; Wręczycki, Mariusz (Quality in Sport, 2026)
Background: Insulin resistance is a key metabolic disorder underlying the development of type 2 diabetes and other cardiometabolic diseases. Lifestyle factors, particularly physical activity, play an important role in improving insulin sensitivity and overall metabolic health. Numerous studies indicate that regular exercise influences glucose metabolism through multiple physiological and molecular mechanisms. Aim: The aim of this review was to summarize current evidence on the relationship between physical activity and insulin sensitivity, with particular emphasis on the biological mechanisms involved and the effects of different types of exercise. Materials and Methods: A PubMed search of English-language studies published in the last 10 years was conducted to evaluate the effects of physical activity on insulin sensitivity and metabolic health. Results: The reviewed studies indicate that both acute and long-term physical activity improve insulin sensitivity through multiple mechanisms, including increased glucose uptake in skeletal muscle, enhanced mitochondrial function, and reduction of visceral adipose tissue. Aerobic exercise, resistance training, and high-intensity interval training are all associated with beneficial metabolic effects. In addition, reducing sedentary behavior and increasing daily activity may further improve glucose metabolism. Conclusions: Regular physical activity represents an effective non-pharmacological strategy for improving insulin sensitivity and preventing metabolic diseases. The greatest benefits appear to result from long-term lifestyle interventions combining exercise, healthy diet, and weight management.